2019
DOI: 10.1029/2019gl083490
|View full text |Cite
|
Sign up to set email alerts
|

The Bunce Fault and Strain Partitioning in the Northern Lesser Antilles

Abstract: Strain partitioning related to oblique plate convergence has long been debated in Northern Lesser Antilles. Geophysical data acquired during the ANTITHESIS cruises highlight that the sinistral strike‐slip Bunce Fault develops along the vertical, long, and linear discontinuity between the sedimentary wedge and a more rigid backstop. The narrowness of the 20‐ to 30‐km‐wide accretionary wedge and its continuity over ~850 km is remarkable. The Bunce Fault extends as far south as 18.5°N where it anastomoses within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Ten Brink and Lin (2004) proposed that the change in the distance of the strike-slip fault to the trench between Puerto Rico and Hispaniola is caused by variations in the Coulomb stresses in the forearc region by the shift in the slip direction due to the change in the direction of the margin to an E-W trending. Laurencin et al (2019), based on data taken in the northern Lesser Antilles, showed that the 850-km-long Bunce Fault is a structural boundary separating the very narrow, sediment-starved trench. They proposed, in a long-term margin erosion, an alternative scenario of a strike-slip system that initiated at greater distance from the trench, at the rear of an initially larger and progressively eroded accretionary domain.…”
Section: Oblique Subduction Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten Brink and Lin (2004) proposed that the change in the distance of the strike-slip fault to the trench between Puerto Rico and Hispaniola is caused by variations in the Coulomb stresses in the forearc region by the shift in the slip direction due to the change in the direction of the margin to an E-W trending. Laurencin et al (2019), based on data taken in the northern Lesser Antilles, showed that the 850-km-long Bunce Fault is a structural boundary separating the very narrow, sediment-starved trench. They proposed, in a long-term margin erosion, an alternative scenario of a strike-slip system that initiated at greater distance from the trench, at the rear of an initially larger and progressively eroded accretionary domain.…”
Section: Oblique Subduction Domainmentioning
confidence: 99%
“…However, they pointed out that the Bunce Fault proximity to the trench might be primarily controlled by the major mechanical weakness at the toe of the prism backstop. The hypothesis proposed by Laurencin et al (2019) is only applicable to the east of the Mona Rift since there is only one transcurrent structure, the BFZ. However, in the OSD there are two parallel transcurrent fault systems (SOFZ and BFZ) coexisting along 170 km, which accommodate oblique convergence in this area forming broad transpressive belts.…”
Section: Oblique Subduction Domainmentioning
confidence: 99%
“…The outer forearc domain corresponds with an interpreted transition zone made of imbricated and underplated material or damage upper plate igneous basement covered with deep forearc sedimentary basins (Bangs et al, 2003;Evain et al, 2013;Laigle et al, 2013) ( Figure 2). To the northwest of Barbuda Island, the trench-parallel left-lateral strike-slip Bunce Fault separates the accretionary wedge from the outer forearc (Laurencin et al, 2019), ( Figure 1 and Figure 2). This fault accommodated the left-lateral component of the plate convergence, revealing active strain partitioning along the oblique plate boundary to the northwest of Barbuda (Laurencin et al, 2019;ten Brink and Lin, 2004).…”
Section: Geological Settingsmentioning
confidence: 99%
“…To the northwest of Barbuda Island, the trench-parallel left-lateral strike-slip Bunce Fault separates the accretionary wedge from the outer forearc (Laurencin et al, 2019), ( Figure 1 and Figure 2). This fault accommodated the left-lateral component of the plate convergence, revealing active strain partitioning along the oblique plate boundary to the northwest of Barbuda (Laurencin et al, 2019;ten Brink and Lin, 2004). Farther west, at the Puerto Rico and the Virgin Islands (PRVI) Margin, the Bunce and Bowin left-lateral strike-slip faults connect to the northern Hispaniola lithospheric transpressive faults, which bound the Bahamas Bank -Hispaniola collisional system (Mann et al, 2005;Rodríguez-Zurrunero et al, 2019;ten Brink and Lin, 2004).…”
Section: Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation